Ocular sequelae of congenital toxoplasmosis in Brazil compared with Europe. - Ruth E Gilbert; Katherine Freeman; Eleonor G Lago; Lilian M G Bahia-Oliveira; Hooi Kuan Tan; Martine Wallon; Wilma Buffolano; Miles R Stanford; Eskild Petersen; European Multicentre Study on Congenital Toxoplasmosis (EMSCOT) (Public Library of Science (PLoS), 2008)
BACKGROUND:Toxoplasmic retinochoroiditis appears to be more severe in Brazil, where it is a leading cause of blindness, than in Europe, but direct comparisons are lacking. Evidence is accumulating that more virulent genotypes of Toxoplasma gondii predominate in South America. METHODS:We compared prospective cohorts of children with congenital toxoplasmosis identified by universal neonatal screening in Brazil and neonatal or prenatal screening in Europe between 1992 and 2003, using the same protocol in both continents. RESULTS:Three hundred and eleven (311) children had congenital toxoplasmosis: 30 in Brazil and 281 in Europe, where 71 were identified by neonatal screening. Median follow up was 4.1 years in Europe and 3.7 years in Brazil. Relatively more children had retinochoroiditis during the first year in Brazil than in Europe (15/30; 50% versus 29/281; 10%) and the risk of lesions by 4 years of age was much higher: the hazard ratio for Brazil versus Europe was 5.36 (95%CI: 3.17, 9.08). Children in Brazil had larger lesions, which were more likely to be multiple and to affect the posterior pole (p<0.0001). In Brazil, visual impairment (<6/12 Snellen) was predicted for most affected eyes (87%, 27/31), but not in Europe (29%; 20/69, p<0.0001). The size of newly detected lesions decreased with age (p = 0.0007). CONCLUSIONS:T. gondii causes more severe ocular disease in congenitally infected children in Brazil compared with Europe. The marked differences in the frequency, size and multiplicity of retinochoroidal lesions may be due to infection with more virulent genotypes of the parasite that predominate in Brazil but are rarely found in Europe.